2018
DOI: 10.1038/gim.2017.142
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive use of extended exome analysis improves diagnostic yield in rare disease: a retrospective survey in 1,059 cases

Abstract: PurposeWe sought to determine the analytical sensitivity of several extended exome variation analysis approaches in terms of their contribution to diagnostic yield and their clinical feasibility.MethodsWe retrospectively analyzed the results of genetic testing in 1,059 distinct cases referred for exome sequencing to our institution. In these, we routinely employed extended exome analysis approaches in addition to basic variant analysis, including (i) copy-number variation (CNV) detection, (ii) nonconsensus spl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
59
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 14 publications
3
59
0
Order By: Relevance
“…Therefore, we highly recommended WES in 2018, and more patients underwent WES than Panel (172 vs 34). The positive rate of WES in this study was 36.6% (63/172), which is consistent with our previous study (38.7%, 12/31)29 and a large cohort study that included 1059 patients by Bergant et al (42.2%) 32. Notebaly, 248 pediatric patients underwent NGS during the incorporation time, and 28 patients were excluded.…”
supporting
confidence: 91%
“…Therefore, we highly recommended WES in 2018, and more patients underwent WES than Panel (172 vs 34). The positive rate of WES in this study was 36.6% (63/172), which is consistent with our previous study (38.7%, 12/31)29 and a large cohort study that included 1059 patients by Bergant et al (42.2%) 32. Notebaly, 248 pediatric patients underwent NGS during the incorporation time, and 28 patients were excluded.…”
supporting
confidence: 91%
“…Concerning mtDNA analysis, only one study on this topic was published: Bergant et al re‐evaluated a cohort of 1.059 ES cases of which 39% ( n = 413) of cases had a neurological referral indication in the broadest sense in. They diagnosed three additional mtDNA mutations (2× m.3243A>G (60% heteroplasmy), referral indication MELAS; 1× m.14598T>C (22%heteroplasmy) referral indication LHON) hereby increasing the diagnostic yield by 0.3% …”
Section: Discussionmentioning
confidence: 99%
“…They diagnosed three additional mtDNA mutations (2× m.3243A>G (60% heteroplasmy), referral indication MELAS; 1× m.14598T>C (22%heteroplasmy) referral indication LHON) hereby increasing the diagnostic yield by 0.3%. 9 First, we aimed to evaluate the feasibility of analyzing the mtDNA by ES in a diagnostic context. We showed that we were able to increase the overall diagnostic yield in a cohort including non-neurological disease by 1.8% even in a setting where targeted mtDNA analyses were used prior to ES in clinical cases with a high suspicion of a certain pathogenic mtDNA variant (eg, LHON, MELAS).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations